2017
DOI: 10.1111/flan.12304
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parental Support and Family Variables in L1 and L2 Vocabulary Development of Japanese Heritage Language Students in the United States

Abstract: This study investigated the role of parental support and selected family variables in the first (L1) and second language (L2) vocabulary development of Japanese heritage language (JHL) high school students in the United States. Eighty‐two JHL students ages 15–18 from eight hoshuukoo (i.e., supplementary academic schools for Japanese‐speaking children) were assessed for their L1 Japanese and L2 English vocabulary knowledge. Simultaneously, the students’ parents, at least one of whom was a Japanese native, compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…Therefore, home language input may vary across families for these DLL children. Moreover, home language input from parents was found to be positively related to young DLLs’ home language outcomes ( Dixon et al, 2012 ; Mori and Calder, 2017 ; Sun et al, 2020 ). Language input and output should be treated equally as a learning process for DLL children.…”
Section: Parental Perceptions Of Bilingualism and Home Language Devel...mentioning
confidence: 97%
“…Therefore, home language input may vary across families for these DLL children. Moreover, home language input from parents was found to be positively related to young DLLs’ home language outcomes ( Dixon et al, 2012 ; Mori and Calder, 2017 ; Sun et al, 2020 ). Language input and output should be treated equally as a learning process for DLL children.…”
Section: Parental Perceptions Of Bilingualism and Home Language Devel...mentioning
confidence: 97%
“…Parent factors related to language practices include: parents’ home language input and parents’ language proficiency. Parents’ home language input includes: parents’ direct input by speaking; and teaching their home language to their children and indirect input through the use of books, television, radio, videos and games (Biedinger et al, 2015; DeCapua & Wintergerst, 2009; Keh & Stoessel, 2017; Kim & Pyun, 2014; Mori & Calder, 2017; Verdon & McLeod, 2015; Verdon et al, 2014). Parents’ language proficiency was also found to affect children’s use of home language (Biedinger et al, 2015; Gollan et al, 2014; Saravanan, 2001).…”
Section: Factors Associated With Home Language Proficienncy and Usementioning
confidence: 99%
“…Hence, one of the goals of JHL research involving multilingual youth is to identify familial, educational, and sociocultural factors contributing to the creation of environments where multilingual literacy is nurtured (e.g., Lauwereyns, 2011). Mori and Calder (2017), for instance, demonstrated that parental support and their effort to establish good family reading habits had a positive impact on their children's development of Japanese as a home/heritage language, and that supporting home language literacy did not in the least hinder the development of the mainstream language (i.e., English in this study). Further, they reported that JHL development was influenced by parental involvement, whereas English proficiency was accounted for by families’ future residency plans and the amount of interaction by the children in English.…”
Section: Social Dimensions Of L2 Japanese Developmentmentioning
confidence: 50%
“…To explore JHL learners’ language development, various factors, including age, length of residence, age of arrival, language abilities, and familial, educational, and sociocultural variables, have been investigated (e.g., Oriyama, 2010, 2011; Doerr & Lee, 2012; Hayashi & Murphy, 2013; Mori & Calder, 2013, 2017; Kurata, 2015; Nakajima & Sano, 2016; Liu, 2018a). Mori and Calder (2013), for example, demonstrated that JHL high school students who came to the United States by age nine were three grades behind in Japanese vocabulary knowledge and were at their grade level in English, whereas those who arrived at age ten or older were at their grade level in Japanese and two to five years behind in English.…”
Section: Social Dimensions Of L2 Japanese Developmentmentioning
confidence: 99%